2017
DOI: 10.1016/j.sjbs.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Xanthium strumarium seed extracts on different cancer cell lines and Aedes caspius , Culex pipiens (Diptera: Culicidae)

Abstract: Effects of methanol extracts of on different cancer cell lines and on the mortality rates of (Diptera: Culicidae) were investigated. Among the cell lines tested, the Jurkat cell line was the most sensitive to the methanol extract and ethyl acetate fraction, with reported LC values of 50.18 and 48.73 μg/ml respectively. Conversely, methanol extracts were not that toxic to the A549 cell line though the toxicity increased on further purification. The percentage of growth inhibition was dose dependent for the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
(18 reference statements)
0
24
0
Order By: Relevance
“…In contrast, other studies reported insecticidal activity from Clausena anisata extract with an LC 50 value of 59.65 ppm in 24 h (Mukandiwa et al, 2015), Xanthium strumarium seed extract with an LD 50 of 531.07 ppm against Aedes caspius and 502.32 ppm for Cx. pipiens larvae (Mekhlafi et al, 2017), and methanolic extract from the leaves of Crataeva magna with LC 50 values of 121.69, 132.09, and 147.27 ppm for Anophelles stephensi, Ae. aegypti, and Cx.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies reported insecticidal activity from Clausena anisata extract with an LC 50 value of 59.65 ppm in 24 h (Mukandiwa et al, 2015), Xanthium strumarium seed extract with an LD 50 of 531.07 ppm against Aedes caspius and 502.32 ppm for Cx. pipiens larvae (Mekhlafi et al, 2017), and methanolic extract from the leaves of Crataeva magna with LC 50 values of 121.69, 132.09, and 147.27 ppm for Anophelles stephensi, Ae. aegypti, and Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Seed, fruit, leaf, root, and whole plant extracts are reported for different biological activities . Phytochemicals such as sesquiterpene lactones, polysterols, phenols, and glycosides are responsible for different biological activities . Stress applied on the graphite particles by sonication is transmitted in the sp hybridized carbons of the graphene planes.…”
Section: Resultsmentioning
confidence: 99%
“…Xanthium strumarium is a traditional medicinal plant with many human health beneficial properties such as antiseptic, anti-inflammatory, water retention, and treating kidney, liver, heart, and depression. 37,38 Seed, fruit, leaf, root, and whole plant extracts are reported for different biological activities. 39,40 Phytochemicals such as sesquiterpene lactones, polysterols, phenols, and glycosides are responsible for different biological activities.…”
Section: Synthesis and Characterization Of Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Mekhlafi et al [37] and Al-Mekhlafi [38] showed that the EtOAc fractions of Xanthium strumarium (Asteraceae) seeds and Carum copticum (Apiaceae) fruits appear to have a weak larvicidal activity. On the contrary, the methanol extracts showed the best results (LD 50 = 502.32 µg/ mL and 122.26 µg/mL, respectively).…”
Section: Discussionmentioning
confidence: 99%